Biliary Peritonitis in a Dog after Perforation of the Gallbladder during Laparoscopic Cholecystectomy - Linhares, Marcella Teixeira; Milech, Vanessa; Martins, Letícia Reginato; Antunes, Bernardo Nascimento; Cadiñanos, Vinícius da Silva; Fischborn, Nadine Trinks; Brun, Maurício Veloso (Acta Scientiae Veterinariae, 2022)
Background: Iatrogenic gallbladder perforation during laparoscopic cholecystectomy (LC) is a common complication and occurs in at least one third of human patients undergoing LC. This is attributed to the fragility of the gallbladder wall associated with mucocele and cholecystitis, in addition to the need for repetitive gripping and traction of the gallbladder during its manipulation with laparoscopic instruments. As complications from this event are rare in human patients, conversion to laparotomy is not routinely indicated and the adverse consequences of bile spillage are minimized by abundant irrigation of the peritoneal cavity and adequate antimicrobial therapy. On the other hand, there is little information regarding the outcome of laparoscopic management of this complication in laparoscopic cholecystectomies in dogs, particularly since most surgeons indicate conversion in these cases. Thus, we describe a case of biliary peritonitis that developed in a dog after laparoscopic management of iatrogenic perforation of the gallbladder during a laparoscopic cholecystectomy, in a case of gallbladder mucocele. To the best of our knowledge, there are no reports of biliary peritonitis following laparoscopic management of iatrogenic gallbladder perforation during LC in dogs. Case: A 14-year-old Poodle was referred for clinical evaluation with selective appetite, recurrent episodes of hyporexia, and abdominal discomfort. Ultrasound findings characterized chronic liver disease and gallbladder mucocele. The patient was referred for laparoscopic cholecystectomy, during which the gallbladder was iatrogenically perforated, with extravasation of a large volume of bile content. This complication was managed by copious abdominal irrigation via laparoscopic access and antimicrobial therapy. On the second postoperative day, the patient started to present apathy, hyporexia, emesis, and jaundice. The patient remained hospitalized in the intensive care unit for stabilization and monitoring through hematological examinations and serial abdominal ultrasound. Due to progressive worsening of the clinical picture, an exploratory laparotomy was performed ten days after the initial surgical procedure. This examination showed multiple adhesions and the presence of bile residues adhered to numerous points on the peritoneal surface. Despite the intensive treatment instituted, death occurred 10 h after the second surgical procedure. Discussion: The high risk of gallbladder perforation during laparoscopic cholecystectomies correlates with the dissection step or repetitive grasping and traction of the gallbladder with laparoscopic instruments. Conversion is not routinely indicated and laparoscopic management is considered effective in humans. However, in this case, the presence of a large volume of extravasated semisolid bile content and its adherence to the mesothelial surface made it impossible to remove it in its entirety despite the abundant irrigation of the abdominal cavity, resulting in a picture of biliary peritonitis in the postoperative period. In view of the reported negative outcome, the authors encourage the adoption of measures that minimize the risk of gallbladder perforation when performing LC in dogs. These include the use of atraumatic instruments or aspiration of bile content before surgical manipulation. Cases in which such a complication is recorded should be carefully monitored to enable early diagnosis and treatment of biliary peritonitis. Furthermore, conversion should be considered when there is extravasation of large volumes of bile, particularly in the presence of gallbladder mucocele, until future studies establish the safety and effectiveness of laparoscopic management of this complication. Keywords: gallbladder mucocele, minimally invasive surgery, laparoscopic cholecystectomy, dogs.